AB0195 Type 2 Innate Lymphoid Cell Counts Are Increased in Patients with Systemic Sclerosis and Correlate with the Extent of Fibrosis. (9th June 2015) - Wohlfahrt, T.; Usherenko, S.; Dees, C.; Palumbo-Zerr, K.; Beyer, C.; Gelse, K.; Distler, O.; Schett, G.; Distler, J.H.; Ramming, A.
Abstract : Background: Type 2 innate lymphoid cells (ILC2), a recently identified population of cells with lymphoid morphology lacking re-arranged antigen-specific receptors, provide a potent source of cytokines and promote type 2 immunity and tissue remodeling. Objectives: Although findings in animal models of fibrotic diseases such as CCl4 -induced liver fibrosis and Schistosoma mansoni -induced pulmonary fibrosis demonstrate increased numbers of ILC2 in fibrotic lesions, data on ILC2 in humans are mainly limited to allergic diseases and largely focus on circulating ILC2. However, the contributive role of ILC2 cells in the pathogenesis of systemic sclerosis (SSc) is unknown. We aimed to evaluate the levels and correlations with fibrotic manifestations in SSc. Methods: Fifty-four patients with SSc and 28 healthy controls were included into the study. Blood samples and skin sections were analyzed by flow cytometry and immunohistochemically. ILC2 counts were correlated to clinical manifestations. Results: ILC2 numbers were elevated by 10 fold in the skin of SSc patients compared to healthy controls assessed by two complementary sets of established markers for ILC2, both of which yielded comparable results. Furthermore, increased numbers of ILC2 were detectable in the skin as well as in the blood of SSc patients and our data also suggest that ILC2 may be involved in the pathogenesis of fibrosis in SSc by showing multiple associations of ILC2 counts with fibrotic manifestations in SSc patients. Stratification of the SSc population in patients with limited (lcSSc) and diffuse cutaneous SSc (dcSSc) demonstrated increased levels of ILC2 in both subgroups with significantly higher frequencies in dcSSc compared to lcSSc. Moreover, dermal and circulating ILC2 counts correlated closely with the modified Rodnan skin score and with the presence of pulmonary fibrosis. Conclusions: Here, we provide first evidence for a role of ILC2 in the pathogenesis of rheumatic diseases by demonstrating increased ILC2 counts in the skin of patients with SSc as compared to healthy individuals. Correlations of ILC2 counts with dermal and pulmonary fibrosis encourage follow-up studies to further evaluate the potential of ILC2 as biomarkers for fibrosis in SSc patients and to characterize the potential of targeting ILC2 as an anti-fibrotic approach in SSc. Disclosure of Interest: None declared